A Method for High Resolution Imaging of Creatine In vivo using Chemical Exchange Saturation Transfer (CrCEST) - Kogan, Feliks (2013)
PURPOSE: To develop a chemical exchange saturation transfer (CEST) based technique to measure free creatine (Cr) and to validate the technique by measuring the distribution of Cr in muscle with high spatial resolution before and after exercise. METHODS: Phantom studies were performed to determine contributions from other creatine kinase metabolites to the CEST effect from Cr (CrCEST). CEST, T(2), magnetization transfer ratio (MTR) and (31)P magnetic resonance spectroscopy (MRS) acquisitions of the lower leg were performed before and after plantar flexion exercise on a 7T whole-body MR scanner on healthy volunteers. RESULTS: Phantom studies demonstrated that while Cr exhibited significant CEST effect there were no appreciable contributions from other metabolites. In healthy human subjects, following mild plantar flexion exercise, increases in CrCEST were observed, which recovered exponentially back to baseline. This technique exhibited good spatial resolution and was able to differentiate differences in muscle utilization among subjects. CrCEST results were compared with (31)P MRS results showing good agreement in the Cr and PCr recovery kinetics. CONCLUSION: Demonstrated a CEST based technique to measure free creatine changes in in vivo muscle. CrCEST imaging can spatially map changes in creatine concentration in muscle following mild exercise. This may serve as a tool for the diagnosis and treatment of various disorders affecting muscle.